DAMPAK KEBIJAKAN KEPALA SEKOLAH DALAM STRATEGI PEMASARAN PENDIDIKAN TERHADAP PENINGKATAN PESERTA DIDIK DI MI PUI KUNINGAN - Lilis Lisdayanti; Dedi Djubaedi; Didin Nurul Rosidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT The principal as a leader has educational roles and policies for the success of an educational institution, one of the policies is the marketing promotion of educational services to increase students. The goal of marketing is to maximize consumer satisfaction and the school will always have its existence. With the existence of several forms of educational marketing, it is hoped that it can measure the success of educational marketing strategies in increasing new students. The aim of this research is to (1) explain the principal's policy regarding educational marketing strategies in increasing the number of students at MI PUI Kuningan, (2) Explain the implementation of the principal's policy regarding educational marketing strategies in the development of increasing the number of students at MI PUI Kuningan, (3) ) explains the impact of the principal's policy in educational marketing strategies on increasing students at MI PUI Kuningan. The researcher used a qualitative approach, the key information in this research was the principal, 3 senior teachers, administrative staff, and the students' parents. The method used in this research is a descriptive method which aims to provide a systematic, factual, accurate description of the facts and nature and relationships between the phenomena being investigated. The conclusion of this research is: The principal's policy regarding educational marketing strategies in increasing the number of students at MI PUI Kuningan with target market strategies, competitive positions, and mixed strategies or marketing mix (7 Ps: product, price, place, promotion, people, physical evidence, process). Implementation of the school principal's policy in the development of increasing the number of students is the preparation of marketing plans carried out by the School Principal and the Foundation determining the target number of students, target areas for marketing, promotional strategies to be carried out, planning for the opening of student admissions. in organizing marketing, forming a committee for accepting new students (PPDB). Implementation process: orientation of new students, class grouping of students. control and control: the school principal acts as a supervisor, as well as being responsible for the PPDB committee referring to planning strategies. The impact of this: increasing public trust in educational institutions, providing excellent service to customers, providing support and cooperation from partners, and a commitment to loyalty from the community, especially parents of students who are loyal customers. Keywords: Principal Policy, Education Marketing, Student Improvement